(untitled) (Eurasian Medical Research Periodical, 2022)
Violation of the vaginal microbiota – bacterial vaginosis has clinical significance due to a variety of adverse factors, the main of which are reproductive outcomes and an increased risk of acquiring sexually transmitted infections. Treatment of bacterial vaginosis causes significant difficulties, especially during pregnancy, since the use of antibacterial therapy negatively affects lactobacilli, forming the risk of recurrent recurrence of the disease. The use of differentiated correction of vaginal microbiocenosis significantly improves treatment outcomes and reduces the number of recurrences of bacterial vaginosis in women during pregnancy